Historical Aspects of Neurosurgery in Sudan, Prof. Abusalih as the Pioneer of Evolution - Mohammed Awad Elzain; Abubakr Darrag Salim Ahmed; Husain Suliman Abusalih (Advanced Concepts in Medicine and Medical Research Vol. 1, 2023)
Introduction: The proper neurosurgical practice started in Sudan by Dr. Abusalih 1971. Before that the neurosurgical practice in Sudan was shouldered by general and orthopedic surgeons who only used to manage some simple neurosurgical problems. Despite the lack of proper diagnostic and operative equipment at that time, wide variety of neurosurgical problems have been adequately managed. Objectives: To describe the effectiveness of diagnostic and operative methods, the quantity and quality of neurosurgical cases operated at that time and to assess the overall outcome of management. Materials and Methods: Retrospective review of the cases records was mainly obtained from Dr. Abusalih book “Neurosurgery in Sudan in the seventies” besides contacting some doctors who attended that period. Results: During the period between 1970 to 1980, 2315 neurosurgical cases were seen. Of these 88% were traumatic brain injuries, 3.8% brain tumors, 1.5% cerebrovascular malformations, 4.1% spinal cases and 2.6% extra-cranial and cranial masses. Discussion: Most brain tumor cases improved postoperatively (68.5%). Most cerebral malformation cases were managed medically. For the spinal tumor cases all benign tumors showed complete recovery while malignant ones showed only partial recovery. The extra-cranial and cranial masses were mainly neoplastic 38.3% and congenital 31.7%. The commonest brain, spinal and extracranial masses were the meningioma. Conclusion: Despite the lack of personnels and the advanced diagnostic and surgical tools, many neurosurgical problems have been adequately dealt with. The recognition of the first steps in the development of neurosurgery will help us to better appreciate the past and aid in its progress in the future.